Biotic interactions affect the colonization behavior of aquatic detritivorous macroinvertebrates in a heterogeneous environment. (5th May 2015) - Verschut, Thomas A.; Meineri, Eric; Basset, Alberto
Abstract: It has previously been suggested that macroinvertebrates actively search for suitable patches to colonize. However, it is not well understood how the spatial arrangement of patches can affect colonization rates. In this study, we determined the importance of the environmental factors (distance, connectivity and resource availability) for patch colonization in an experimental system using Gammarus aequicauda (Amphipoda), Lekanesphaera hookeri (Isopoda) and Ecrobia ventrosa (Gastropoda). Furthermore, we also assessed how the relative importance of each of these environmental factors differed in interactions between the three species. The single species experiments showed that distance was the most important factor for G. aequicauda and E. ventrosa . However, while E. ventrosa preferred patches close to the release point, G. aequicauda strongly preferred patches further from the release point. High resource availability was a strong determinant for the patch colonization of G. aequicauda and L. hookeri. Connectivity was only of moderate importance in the study system for L. hookeri and E. ventrosa . The effects of the environmental factors were strongly affected by interspecific interactions in the multispecies experiments. For G. aequicauda, the distance preference was lowered in the presence of E. ventrosa . Moreover, while for L. hookeri the effect of resource availability was ruled out by the species interactions, resource availability gained importance for E. ventrosa in the presence of any of the other species. Our results suggest a strong link between environmental factors and biotic interactions in the colonization of habitat patches and indicate that the effect of biotic interactions is especially important for species sharing similar traits. Graphical abstract: Highlights: We test the influence of biotic interactions in colonization behavior. Species respond in specific ways to spatial heterogeneity. Responses in colonization behavior depend on species' traits. Biotic interactions are able to affect colonization behavior.